Hypertension: high prevalence and a positive association with obesity among Aboriginal and Torres Strait Islander youth in far north Queensland - Danielle Esler; Alexandra Raulli; Rohan Pratt; Patricia Fagan (Elsevier, 2016)
Abstract Objective: Hypertension and other chronic disease risks are common among Aboriginal and Torres Strait Islander adults but there is little evidence regarding the epidemiology of these risk factors during adolescence. This study examines the prevalence of pre‐hypertension, hypertension and other cardiovascular risk factors in Aboriginal and Torres Strait Islander people aged 15-24 years living in remote Indigenous communities in north Queensland. In so doing, it aims to better inform the approach to cardiovascular disease in this population. Methods: This is a descriptive study that retrospectively examines health service data from a program of community screening, the Young Persons Check (YPC). Participants were 1,883 Aboriginal and Torres Strait Islander people aged 15-24 years who attended for a YPC in 11 remote communities in north Queensland between March 2009 and April 2011. Results: Overall, the prevalence of pre‐hypertension was 34.0%; stage I hypertension was 17.7% and stage II hypertension was 3.3%. The prevalence of elevated waist circumference was 47.6%, overweight or obesity 45.9%, elevated triglycerides 18.3%, decreased HDL 54.8% and proteinuria 24.3%. The prevalence of hypertension (stage I or II) among Torres Strait Islander males was 34.1%, Aboriginal males 26.9%, Torres Strait Islander females 12.6% and Aboriginal females 13.0%. Hypertension was associated with sex (males) (OR= 4.37, p<0.000), overweight (OR=2.46, p<0.000), obesity (OR=4.59, p<0.000) and elevated triglycerides (OR=2.38, p<0.000). Conclusion: Pre‐hypertension, hypertension and other cardiovascular risk in this population is highly prevalent. Hypertension was particularly prevalent among male participants. The results reiterate the importance of early life experience in cardiovascular disease prevention.